1997
DOI: 10.2105/ajph.87.9.1519
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of cigarette prices and no-smoking bylaws to the prevalence of smoking in Canada.

Abstract: OBJECTIVES: The aim of this study was to analyze the association of cigarette prices and no-smoking bylaws with the prevalence of smoking. METHODS: Data on individual smoking status were taken from two national household surveys in Canada. Current cigarette price, the 1-year and 10-year increase in price, and the extent of local restrictions on public smoking were added to the model. Logistic regression was used to estimate the odds of being a smoker. RESULTS: The odds ratio for being a smoker was 1.21 where n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 4 publications
3
27
0
Order By: Relevance
“…Socio-demographics were critical variables in Alberta, while in Ontario structural factors were most important. This is consistent with other work suggesting that different contextual factors are at play in municipal decision-making around having a bylaw and in the level of protection it will offer [12,25,26]. In other words, the decision to pass "any" bylaw may be related to a different combination of community variables than the decision to implement a "strong" bylaw.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Socio-demographics were critical variables in Alberta, while in Ontario structural factors were most important. This is consistent with other work suggesting that different contextual factors are at play in municipal decision-making around having a bylaw and in the level of protection it will offer [12,25,26]. In other words, the decision to pass "any" bylaw may be related to a different combination of community variables than the decision to implement a "strong" bylaw.…”
Section: Discussionsupporting
confidence: 90%
“…Finally, some variation in bylaw composition may be explained by the influence of local ecological factors, or community characteristics. Sociodemographics, geographic region, or smoking rates, for example, have been reported to play a role in the development and strength of municipal smoke-free bylaws [12,[22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Strong local ordinances in California in 1990-1 were associated with anabsolute quit rate (over the previous six months) 7.6% higher than in areas with no workplace laws 86. A Canadian study in 1990-1 found a 21% reduction in the odds of being a smoker in areas with high versus low coverage of smoking bylaws 89. A 1995 Finnish law that prohibited smoking in public areas in workplaces(with the option of creating separately ventilated smoking rooms) was associated with a 4.5% drop in prevalence of smoking and three fewer cigarettes smoked per day among continuing smokers 57…”
Section: Discussionmentioning
confidence: 99%
“…By implementing those measures 26,27 it is possible to reduce tobacco use on a societal level and therefore facilitate change on an individual level.…”
Section: Environmental Determinantsmentioning
confidence: 99%